Case Report: Radiation necrosis mimicking tumor progression in a patient with extranodal natural killer/T-cell lymphoma - Chen, Boxiao; Fan, Yili; Wang, Luyao; Zhang, Jiawei; Xin, Dijia; Qiu, Xi; Jiang, Huawei; Li, Baizhou; Chen, Qin; Wang, Chao; Xiao, Xibin; Huang, Liansheng; et al. (Frontiers in Radiology, 2023)
Radiation-induced cerebral necrosis, also known as radiation encephalopathy, is a debilitating condition that significantly impacts the quality of life for affected patients. Secondary central nervous system lymphoma (SCNSL) typically arises from highly aggressive mature B-cell lymphoma, but rarely from extranodal natural killer T-cell lymphoma (ENKTL). Treatment will be guided by differentiation between lymphoma progression from brain necrosis, and is particularly important for critically ill patients in an acute setting. However, differential diagnosis remains challenging because they share similar clinical manifestations and have no specific imaging features. We present the case of a 52-year-old man with ENKTL who suffered an emergency brain herniation secondary to massive radiation necrosis. The diagnosis established by brain biopsy ultimately led to appropriate treatment. The importance of the diagnostic biopsy is highlighted in this case for distinguishing between radiation necrosis and SCNSL.